2020
DOI: 10.1007/s11357-020-00202-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of multi-domain cognitive aging in participants of the Long Life Family Study

Abstract: Maintaining good cognitive function at older age is important, but our knowledge of patterns and predictors of cognitive aging is still limited. We used Bayesian model-based clustering to group 5064 participants of the Long Life Family Study (ages 49-110 years) into clusters characterized by distinct trajectories of cognitive change in the domains of episodic memory, attention, processing speed, and verbal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…The strong relationship between higher levels of PA and better cognitive function are well-established, [1][2][3][4][5] and our results confirm this association. To the best of our knowledge, our study was the first to investigate this association using a data-driven approach to identify PA trajectories.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The strong relationship between higher levels of PA and better cognitive function are well-established, [1][2][3][4][5] and our results confirm this association. To the best of our knowledge, our study was the first to investigate this association using a data-driven approach to identify PA trajectories.…”
Section: Discussionsupporting
confidence: 86%
“…Physical activity (PA) and cognitive performance (CP) are strongly linked and have been shown to decline with ageing. [1][2][3][4][5] Multiple observational and interventional studies have demonstrated that a higher level of PA is associated with better CP in old age. [6][7][8][9][10][11][12][13][14] However, most of these studies focused on the association between PA levels and CP.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that spatiotemporal parameters such as gait velocity, stride time, and stride length are correlated with cognitive domains of memory, executive function, and attention in the elderly with MCI ( Xie et al, 2019 ). A recent study has shown that faster gait speed was associated with a change in immediate recall but not delayed recall memory ( Sebastiani et al, 2020 ). While another study showed that executive function had a strong correlation with gait speed compared to other cognitive domains in patients with cognitive impairment ( Toots et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous studies that showed a decline of cognitive function with older age in multiple domains ( Harada et al, 2013 ), and the negative effect of APOE e4 on cognitive decline in centenarians ( Arosio et al, 2017 ; Du et al, 2020 ). There is some evidence that, among centenarians, the e2 allele confers protection from cognitive decline ( Kim et al, 2017 ; Sebastiani et al, 2020 ), in addition to increasing the chance for longevity ( Sebastiani et al, 2019a ) and conferring protection from aging-related diseases ( Wolters et al, 2019 ; Kuo et al, 2020 ). Our studies also found that carriers of e2 with low education can delay their onset of moderate cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%